Republic of Congo Investment Climate Policy Note - World Bank (Washington, DC, 2014)
This Investment Climate Policy Note (ICPN) identifies the main constraints to the development of the private sector in the Republic of Congo, based on a survey of enterprises operating in the manufacturing and services sectors, in Pointe Noire and Brazzaville, and to propose specific short term recommendations to address these constraints. The ICPN emphasizes cross-country comparisons and benchmarks the investment climate across various firm characteristics. It is a targeted report focusing on a smaller set of indicators of firm performance and concentrating on certain dimensions of the investment climate. It aims to answer the following key questions: (i) what are the required reforms to improve the investment climate in Congo, (ii) how to prioritize these reforms and (iii) how to implement the priority reforms, what could be the institutional mechanism to drive the reform agenda? The report begins with a discussion of Congo s background, and Chapter 2 describes the investment climate. The last chapter makes recommendations going forward.